Penerapan Sanksi terhadap Pelanggaran Awig-Awig di Desa Adat Bongkasa Pertiwi Kecamatan Abiansemal Kabupaten Badung - A. A. Dwi Ani Agustini; I Made Suwitra; I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2020)
Humans always live side by side and need other creatures to interact each other. They were created as social beings who cannot live alone. This research aims to analyze the existence of ngejot and the application of sanctions for violations in the Bongkasa Pertiwi Traditional Village. This type of research uses an empirical legal research with a sociological approach, a statutory approach, a concept approach and a case approach. The data in this study are primary data, namely data obtained from informants and respondents and secondary data using primary, secondary and tertiary legal materials. The results showed that the existence of ngejot in the Bongkasa Pertiwi Traditional Village, Abiansemal District, Badung Regency, currently prohibits the existence of the tradition of ngejot. Boosting is still a pro and contra in society because pushing is sometimes still practiced as a form (equalizing braya). Over time, the prohibition on driving can change and be adapted to the circumstances because it is flexible. With regard to the sanctions against the prohibition of boasting in the Bongkasa Pertiwi Traditional Village, a penalty of Rp. 1,000,000 (one million rupiah), apikul bass (100 kg) were required to be sinoman for 6 months and apologized in front of the people of Bongkasa Pertiwi Village. Even though the implementation of this ngejot is carried out only to the extent of ngejot aci for the completeness of the ceremony, it must be based on permission through Bendesa Adat.